Analysis of 13-valent pneumococcal polysaccharide conjugate vaccine among children born in Hangzhou from 2017 to 2021 - Che, Xinren; Chen, Qinghua; Liu, Yan; Gu, Lintao; Lu, Zhaojun; Gu, Wenwen; Wang, Jun; Jiang, Wei; Du, Jian; Zhang, Xiaoping; Xu, Yuyang; Zhang, Xuechao; et al. (Frontiers in Public Health, 2023)
Background 13-valent pneumococcal polysaccharide conjugate vaccine (PCV13) has been introduced in Hangzhou since 2017, whereas its current immunization state in children is not clear. Therefore, this study aims to describe the PCV13 vaccination distribution among children born in Hangzhou from 2017 to 2021 to provide data for reducing vaccination differences among different populations. Methods Descriptive epidemiology was used for data analysis and PCV13 vaccination related information of children was collected from children vaccination management system of Zhejiang Province (ZJCVMS). Results Among the 649,949 children born in Hangzhou from 2017 to 2021, 169,230 were vaccinated with an average full course vaccination rate of 26.0%. The full course vaccination rates in 5 years were different (P = 0.000) with an increasing trend (Pfortrend < 0.01). The first dose vaccination rates were different in 5 years (P = 0.000) with an increasing trend (Pfortrend < 0.01). The distribution of age when first dose PCV13 was administered varied, most people at 2 months and least people at 5 months. The full course vaccination rate varied by areas, highest in central urban areas and lowest in remote areas respectively (all P-value < 0.05). Overall, the full course vaccination rate of PCV13 was higher in the registered residence population than the non-registered residence population, which was 136,693 (31.4%) and 32,537 (15.1%) respectively (P = 0.000). The full course vaccination rates were the same between men and women (P = 0.502), which was 87,844 for men (26.0%) and 81,386 for women (26.1%). Conclusion Although the number of people who received PCV13 full course vaccination and received the first dose vaccination showed yearly increasing trends in Hangzhou, the full course vaccination rate for the whole population was relatively low. In addition, the PCV13 vaccination rates also differed by geography and household registration status. Measures such as expanding vaccination publicity or including national immunization should be taken to increase vaccination rates and reduce the differences in vaccination among groups with different characteristics.